Cluster analysis of DCE‐MRI data identifies regional tracer‐kinetic changes after tumor treatment with high intensity focused ultrasound. (21st September 2015) - Jacobs, Igor; Hectors, Stefanie J. C. G.; Schabel, Matthias C.; Grüll, Holger; Strijkers, Gustav J.; Nicolay, Klaas
<x xml:space="preserve">Abstract</x> Evaluation of high intensity focused ultrasound (HIFU) treatment with MRI is generally based on assessment of the non‐perfused volume from contrast‐enhanced T1‐weighted images. However, the vascular status of tissue surrounding the non‐perfused volume has not been extensively investigated with MRI. In this study, cluster analysis of the transfer constant Ktrans and extravascular extracellular volume fraction ve, derived from dynamic contrast‐enhanced MRI (DCE‐MRI) data, was performed in tumor tissue surrounding the non‐perfused volume to identify tumor subregions with distinct contrast agent uptake kinetics. DCE‐MRI was performed in CT26.WT colon carcinoma‐bearing BALB/c mice before (n = 12), directly after (n = 12) and 3 days after (n = 6) partial tumor treatment with HIFU. In addition, a non‐treated control group (n = 6) was included. The non‐perfused volume was identified based on the level of contrast enhancement. Quantitative comparison between non‐perfused tumor fractions and non‐viable tumor fractions derived from NADH‐diaphorase histology showed a stronger agreement between these fractions 3 days after treatment (R2 to line of identity = 0.91) compared with directly after treatment (R2 = 0.74). Next, k‐means clustering with four clusters was applied to Ktrans and ve parameter values of all significantly enhanced pixels. The fraction of pixels within two clusters, characterized by a low Ktrans and either a low or high ve, significantly increased after HIFU. Changes in composition of these clusters were considered to be HIFU induced. Qualitative H&E histology showed that HIFU‐induced alterations in these clusters may be associated with hemorrhage and structural tissue disruption. Combined microvasculature and hypoxia staining suggested that these tissue changes may affect blood vessel functionality and thereby tumor oxygenation. In conclusion, it was demonstrated that, in addition to assessment of the non‐perfused tumor volume, the presented methodology gives further insight into HIFU‐induced effects on tumor vascular status. This method may aid in assessment of the consequences of vascular alterations for the fate of the tissue. Copyright © 2015 John Wiley & Sons, Ltd.